Spectrum of VHL mutations in clear cell renal cell carcinoma - N. N. Mazurenko; I. V. Tsyganova; V. V. Strelnikov; A. V. Balbutsky; T. F. Malivanova; E. B. Kuznetsova; V. A. Draudin-Krilenko; O. V. Shangina; A. F. Mukeria; V. B. Matveev; D. G. Zaridze (Успехи молекулярной онкологии, 2020)
The VHL gene alterations are the early and characteristic feature of clear cell renal cell carcinoma (ccRCC). We have examined VHL mutations in sporadic 98 ccRCC cases to evaluate their localization in relation to functionally important motifs of the VHL protein. The DNA samples were obtained from snap-frozen carcinoma biopsies and used for Sanger sequencing, while 62 ccRCC DNA cases were studied by next generation sequencing (NGS) analysis in parallel. In 73 (74.4 %) оf 98 ccRCC cases the somatic non-silent VHL mutations were identified. Loss of function VHL mutations (nonsilent, frameshifts or in splicing sites) were detected in 40 (40.8 %) ccRCC, while missense mutations – in 35 (35.7 %) ccRCC. In total 76 mutations important for VHL functioning were detected in 72 (73 %) ccRCC samples, of them 15 mutations (deletion / insertion in-frame or frameshifts) were identified for the first time. Four ccRCC cases contained two mutations each. Most of missense mutations disturb the sites of VHL interactions with HIF, РКС or kinesin. The pathogenicity of p.P154P silent mutation and intronic mutations near mRNA VHL splicing sites was discussed. The obtained results are important for understanding the role of VHL mutations in ccRCC progression and prognosis.